Answer:
Ff = 839.05 N
Explanation:
We can use the equation:
Ff = μ*N
where <em>N</em> can be obtained as follows:
∑ Fc = m*ac ⇒ N - F = m*ac = m*ω²*R ⇒ N = F + m*ω²*R
then if
F = 32 N
m = 133 Kg
R = 0.635 m
ω = 95 rev /min = (95 rev / min)(2π rad / 1 rev)(1 min / 60 s) = 9.9484 rad /s
we get
N = 32 N + (133 Kg)*(9.9484 rad /s)²*(0.635 m) = 8390.53 N
Finally
Ff = μ*N = 0.10*(8390.53 N) = 839.05 N
I believe it she should use the first aid kit next
So we need to find the formula for magnetic field B using the current (I) and the distance from the probe (d). So, We know that the stronger the current I, the stronger the magnetic field B. That tells us that the I and B are proportional. Also we know that the strength of the magnetic field B is weaker as the distance d of the probe increases. That tells us that B and d are inversely proportional. So our formula should have B=(I/d)*c where c is a constant of proportionality. c=μ₀/2π where μ₀ is the permeability of free space. So finally our formula is B=(μ₀I)/(2πd).
Answer:
B
Explanation:
hair can be a safety hazard